Navigating the Digital Landscape: Challenges and Barriers to Effective Information Use on the Internet - Jiadong Yu; D. A. Bekerian; Chelsee Osback (Encyclopedia)
The advent of the internet has fundamentally transformed how people access and interact with information. The digital landscape offers easy access to educational materials and healthcare and can support informed decision making. It also presents significant challenges in effectively using this information. This entry discusses the multifaceted barriers that can impede individuals from fully benefiting from the internet’s information resources. Key challenges include discerning between accuracy and misinformation, the uneven distribution of digital literacy, disparities in access to technology, and motivational barriers in seeking reliable information. Additionally, the growing involvement of artificial intelligence (AI) in content curation, regulation, and moderation introduces opportunities and ethical dilemmas. These factors complicate efforts to support the accuracy and trustworthiness of the information shared through digital platforms.